(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Synthetic seeds of cauliflower cv. Chillout were developed by encapsulating mature somatic embryos in neutral gel media. Somatic embryos were obtained by optimizing callus and cell suspension cultures of cauliflower. Friable, yellowish embryogenic calli were obtained on MS supplemented with 2 mg/l 2,4-D and 0.5 mg/l BAP using hypocotyl as explants, while calli were regenerated in media consisting of 5 mg/l BAP, 2 mg/l Kn and 6 mg/l GA3. Somatic embryo-genesis was induced in cell suspension culture where auxins were removed in successive steps triggering conversion of globular cells into the heart, torpedo stage (71%) and finally into cotyledonary/somatic embryos (28%). The mature somatic embryos were encapsulated by mixing mature cell suspension with sodium alginate and calcium chloride mixture (1 : 4). Developed synthetic seeds germinated into complete plantlets when placed in neutral gel media. Germination efficiency of synthetic seeds decreased to about 50 per cent after 12 weeks of storage at 4ºC followed by a rapid decrease to zero per cent after 16 weeks. It was also observed that cauliflower plantlets from synthetic seeds survived successfully when transferred to soil demonstrating that cauliflower synthetic seeds is a promising step towards their in vivo direct use. Plant Tissue Cult. & Biotech. 24(1): 27-36, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19193